Measuring empathy online and moral disengagement in cyberbullying - Francisco, Sofia Mateus; da Costa Ferreira, Paula; Veiga Simão, Ana Margarida; Pereira, Nádia Salgado (Frontiers in Psychology, 2023)
This investigation intends to explore how adolescents report empathy in online contexts and moral disengagement in cyberbullying incidents, and how these two constructs are related. To accomplish this goal, three studies were conducted considering the need to develop new instruments to uncover this new approach of measuring empathy and moral disengagement. In the first study, we adapted the Portuguese version of the Empathy Quotient-short form to online contexts, which resulted in the Empathy Quotient in Virtual Contexts (EQVC). We also developed the Process Moral Disengagement in Cyberbullying Inventory (PMDCI), in order to assess moral disengagement in these specific situations. In the second study we conducted exploratory factor analyses (N=234) of these instruments. Finally, in the third study, we conducted confirmatory factor analyses (N=345) of both instruments. These results showed how adolescents reported empathy in online contexts and moral disengagement in cyberbullying incidents. Specifically, empathy revealed a bi-dimensional structure including difficulty and self-efficacy in empathizing (Cronbach's α = .44, .83, respectively), whereas process moral disengagement revealed four unidimensional questionnaires including locus of behavior, agency, outcome, and recipient (Cronbach's α = .76, .65, .77, .69, respectively). Furthermore, a correlational analysis was also performed of both constructs, and we also considered the variable sex. Results showed that difficulty in empathizing was negatively associated with sex (with girls revealing more difficulty than boys) and all moral disengagement mechanisms except for behavior. Moral disengagement was positively correlated with sex, suggesting boys morally disengaged more from cyberbullying. The instruments provided new insights on how empathy and moral disengagement can be specific to online contexts and cyberbullying situations, and how they can be used in educational programs to promote empathy and gain insight on moral disengagement within this phenomenon.